WORKSHOP INDUSTRI EKONOMI KREATIF DALAM PERSPEKTIF BISNIS - Wisnu Rayhan Adhitya; Yuli Arnida Pohan, Taufiq Risal, Santi Rizki, Jumeida Simatupang, Tika Nirmala Sari, Austin Alexande (Adiba Aisha Amira, 2023)
The developmentof creative industries is one of the goverments efforts in advancing the economy especially the economy in Indonesia. This is Realized by the creative industry of creativity and human wealth done by Indonesia. Creative economy is now a sector that is enough to help the country’s economy. Social media is communication medium that almost owned by every internet user, including for the creative business in Indonesia. So it is unfortunate if this oppurtunity is not utilized by business actors. If businessman usually needs a place and set time in marketing the products and services, now all that can begin tobe eliminated now.